2022
DOI: 10.1093/inthealth/ihac015
|View full text |Cite
|
Sign up to set email alerts
|

Gestational trophoblastic disease and associated factors among women experiencing first trimester pregnancy loss at a regional referral hospital in central Tanzania: a cross-sectional study

Abstract: Background Gestational trophoblastic diseases (GTDs) may follow any form of pregnancy or a pregnancy loss. Early detection of GTDs is important, as some benign forms of the disease may progress into a chemoresistant and metastatic disease. This study aimed at determining the frequency of GTDs among women experiencing first trimester pregnancy loss and the associated patients’ characteristics. Methods This was a cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
1
3
1
1
Order By: Relevance
“…We observed that patients with low parity (i.e., nullipara 15.3%, para-one 17.6% and para two 17.0%) were the major group with GTD. Similar results were found in a regional study at Abbottabad (42% para 0-1) [16], a study in Tanzania 65% of patients were para 0-1 and studies by Fatima et al, Parazzini F et al, Brinton et al, and Saraf and Ghodke, which shows that risk of GTD decreases with increase in parity [9,[20][21][22][23].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We observed that patients with low parity (i.e., nullipara 15.3%, para-one 17.6% and para two 17.0%) were the major group with GTD. Similar results were found in a regional study at Abbottabad (42% para 0-1) [16], a study in Tanzania 65% of patients were para 0-1 and studies by Fatima et al, Parazzini F et al, Brinton et al, and Saraf and Ghodke, which shows that risk of GTD decreases with increase in parity [9,[20][21][22][23].…”
Section: Discussionsupporting
confidence: 86%
“…In this study 80.16% of patients with GTD had RH positive antigen. Jagtap et al [15] reported similar findings (83.11%) and overall blood groups B (33.4%) and O (26.9%) were the most common blood groups in our study, while in a study in Karachi [11] blood group A was reported to be more prevalent (OR=1.6, CI=I.01-2.53); however, international studies found blood group O to be more prevalent (97.8% and 79.3%) [19][20]. In this study blood group, O was found more commonly in the malignant form of disease only.…”
Section: Discussioncontrasting
confidence: 67%
“…This fits with what other studies in Oman, Tanzania, and Egypt found: there was no link between the number of pregnancies, having had a miscarriage before, or blood group and the number of GTDs and their types. [20][21][22] Al Riyami et al ( 2019) also reported no statistical association between GTD and multiparous women, although GTD was observed more in multiparous women. 21 In contrast, Lurain (2010) reported that a history of spontaneous abortion is a reported risk factor for molar pregnancies (both complete and partial).…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, another study also reported that the partial hydatidiform mole was the most common (around 43%) histopathological finding. 20 In addition, Riyamiet al (2019) likewise found that around 55% of the sample was diagnosed with partial hydatidiform mole and approximately 44% of the sample was diagnosed with complete hydatidiform mole. 21…”
mentioning
confidence: 99%
See 1 more Smart Citation